An update on polyethylene and biodegradable plastic mulch films and their impact on the environment. (November 2022) - Somanathan, Harshitha; Sathasivam, Ramaraj; Sivaram, Salini; Mariappan Kumaresan, Sivaniraji; Muthuraman, Meenakshi Sundaram; Park, Sang Un
Abstract: Many ways are being developed in the realm of agriculture to increase crop yield while inflicting minimal damage to the soil and environment. One among them is the application of agricultural, biodegradable mulch (BDM) films. Organic substances or synthetic materials are used for making mulches. Also, bio-based polymers derived from bacteria, microorganisms, or fossil fuels are used to make BDM films. BDM films are used in crop production because of their high agronomical advantages which lead to sustainable agriculture. These films are placed on the soil's surface, around the plants. Mulches help in conserving the moisture, control the temperature of the soil, control the growth of the weed, and help in the utilization of soil nutrients thus, overall enhancing the crop yield. The usage of plastic mulch in agriculture has expanded substantially all around the world, over the past ten years, this is because polyethylene films are cheaper, easily produced, highly flexible, and durable. However, the improper disposal of used plastic films has resulted in soil pollution and environmental contamination. Traditional mulches are replaced by BDM, which is a more environmentally friendly alternative. After being used, degradable mulch films could be tilled into the soil and are expected to disintegrate over time. This review focuses on the BDMs, their history, plastic mulches, how BDMs became an alternative source for plastic mulches, their composition, and also addresses their significance. In addition, we discuss the environmental impact of films, including how it alters the climate, soil, temperature, and weed management. Graphical abstract: Image 1 Highlights: Plastic mulch will cause damage to crops, soil, and the environment. Biodegradable mulch is one of the most important renewable and environmentally friendly materials. There are still many difficult tasks for the development of biodegradable mulch which need to be overcome. Biodegradable mulch and its application have a broad scope in the future.